European Banking System, ESG and Non-performing Loans during the Era of Covid-19: Some theoretical considerations and insights - Kenourgios, D.; John Hlias Plikas (Volume of essays in honour of Professor Apostolos Apostolou, Panteion University, 2022)
Purpose - The purpose of this study is twofold: To provide a general overview of the existing literature circulating the Non-Performing Loans (NPLs) in the European Banking System and to provide evidence of the future of European NPL developments, from the prism of the recent Covid-19 pandemic and the ESG (Environmental, Social, Governance) factors, placing the focus on the Greek banking sector. Design/methodology/approach - The research methodology implemented is a critical overview of the existing literature regarding NPLs, comprising of officially published papers. Due to the fact that both the Covid-19 pandemic & and the ESG factors are very recent, the papers included are mainly of theoretical nature. This paper provides a comprehensive overview of the NPL literature, placing the focus on the implications that the recent worldwide developments will have on NPL flows. Findings - The findings showed that Covid -19 is expected to negative impact the European NPLs. Moreover, the alterations due to the implementation of ESG factors will cause major effects to the European banking system, which are expected to withhold the upcoming the NPL level increase. Originality/value - This paper offers the first attempt, to the best of the authors’ knowledge, by analyzing the existing literature regarding Covid-19 & ESG, expected to have a profound impact on the NPLs stocks. It also provides a general overview of the expected impact of the two prementioned factors in the European NPLs, driven by the relative shortage of relevant research, while offering useful insights which contribute to a deeper understanding.